2021
DOI: 10.3808/jei.202100453
|View full text |Cite
|
Sign up to set email alerts
|

Time Variant Interval Linear Programming for Environmental Management Systems

Abstract: Optimization technology is widely applied to maximize economic profit under ecology constrains in environmental management systems. To tackle the inherent uncertainties, inexact optimization methods have been proposed. Interval linear programming (ILP) model has drawn increasing scholarly attention. ILP model describe uncertainty by one coarse scaled stochastic process. However, uncertainty often involves multiple stochastic processes when zooming into high resolution. ILP model may not satisfied fine scale co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The increasing enrichment of MPs in the shoreline environment poses both ecological and social-economic risks. A systematic and in-depth understanding of the alteration and motion of MPs in the ocean environment is the basis and prerequisite for mitigation of these risks. , Previous studies have focused primarily on the characteristics of MPs under the influence of traditional factors, whereas less attention has been given to NBs in spite of the important role they play in the behavior and motion of MPs. In this study, behavior and motion of various MPs in the presence of NBs were evaluated, as well as the effect of salinity and external energy on the interaction of MPs and NBs.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing enrichment of MPs in the shoreline environment poses both ecological and social-economic risks. A systematic and in-depth understanding of the alteration and motion of MPs in the ocean environment is the basis and prerequisite for mitigation of these risks. , Previous studies have focused primarily on the characteristics of MPs under the influence of traditional factors, whereas less attention has been given to NBs in spite of the important role they play in the behavior and motion of MPs. In this study, behavior and motion of various MPs in the presence of NBs were evaluated, as well as the effect of salinity and external energy on the interaction of MPs and NBs.…”
Section: Resultsmentioning
confidence: 99%
“…Figure compares the carbon cost and the bunker cost based on the bunker price distribution to investigate the relations among speed, bunker consumption, and carbon cost. This study uses various historical bunker data generated to model bunker price uncertainty because of the volatility of bunker prices. , The same Emission Control Area for sulfide encompasses the North Atlantic Ocean from the east coast of Canada to the west coast of Europe; , thus, the price range refers to the historical price of low-sulfur marine gas oil to satisfy the region’s requirements for low-sulfur emissions…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the process, mechanism, and realization path of ES flows (Liu et al, 2017b), ES bundles (Tao et al, 2018), and land sense creation of ES Qin et al, 2022) has become the subject of scholarly attention. Ecosystem processes are altered by changing landscape patterns, resulting in impacts on the ability of ecosystems to produce goods and services (Fu et al, 2014;Li et al, 2015;Zou et al, 2017., Xiong et al, 2018Xiao et al, 2022) The results showed that increasing the land cover of forest, grassland, and canal in the study watershed would maximize the total ESV. Furthermore, the interaction between changes in landscape patterns and ES values was evaluated.…”
Section: Introductionmentioning
confidence: 86%